THE ARTISTIC CHARACTERISTICS OF THE IMAGES OF FATHER AND CHILD IN CORMAC McCARTHY’S ​​“THE ROAD” (International journal of artificial intelligence, 2025)
This article analyzes American writer Cormac McCarthy’s novel “The Road”, highlighting the images of father and son and their spiritual and artistic relationship. In the work, values ​​such as fatherhood, love, morality, and humanity are given new philosophical meaning against the backdrop of the final scene of humanity's destruction. The study reveals the author’s moral, existential, and religious ideas underlying the images of father and son.